Mediation of parental educational level on fruit and vegetable intake among schoolchildren in ten European countries. Issue 1 (9th January 2014) - Lehto, Elviira; Ray, Carola; te Velde, Saskia; Petrova, Stefka; Duleva, Vesselka; Krawinkel, Michael; Behrendt, Isabel; Papadaki, Angeliki; Kristjansdottir, Asa; Thorsdottir, Inga; Yngve, Agneta; Lien, Nanna; et al.
Abstract: Objective: To examine which factors act as mediators between parental educational level and children's fruit and vegetable (F&V) intake in ten European countries. Design: Cross-sectional data were collected in ten European countries participating in the PRO GREENS project (2009). Schoolchildren completed a validated FFQ about their daily F&V intake and filled in a questionnaire about availability of F&V at home, parental facilitation of F&V intake, knowledge of recommendations about F&V intake, self-efficacy to eat F&V and liking for F&V. Parental educational level was determined from a questionnaire given to parents. The associations were examined with multilevel mediation analyses. Setting: Schools in Bulgaria, Finland, Germany, Greece, Iceland, the Netherlands, Norway, Portugal, Slovenia and Sweden. Subjects: Eleven-year-old children ( n 8159, response rate 72%) and their parents. Results: In five of the ten countries, children with higher educated parents were more likely to report eating fruits daily. This association was mainly mediated by knowledge but self-efficacy, liking, availability and facilitation also acted as mediators in some countries. Parents' education was positively associated with their children's daily vegetable intake in seven countries, with knowledge and availability being the strongest mediators and self-efficacy and liking acting as mediators to some degree. Conclusions: Parental educational level correlated positively with children's daily F&V intake in most countries and the pattern of mediation varied among the participating countries. Future intervention studies that endeavour to decrease the educational-level differences in F&V intake should take into account country-specific features in the relevant determinants of F&V intake.